2009
DOI: 10.3855/jidc.144
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Scabies in Iraq: Survey in a Dermatology Clinic

Abstract: Background: The burden of scabies is highest in tropical countries, but recent data from Iraq are scanty. Objective: To estimate the frequency of scabies in patients of a dermatology clinic in central Iraq. Methodology: The study was conducted in Tikrit (Iraq), between May 2007 and February 2008. A total of 1,194 patients presenting to a dermatology clinic were included in the study. Results: During the study period, 132 [1.1%] patients with scabies were identified. The frequency was 13.5% in males and 8.6% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
2
12
4
1
Order By: Relevance
“…This rate was higher than the previously reported studies for different geographical areas in Iraq, as show incidence rate with a range of 1.2% to 6.86% [3,4,5,8,9,11,12]. However, one study [10] reported incidence rate of 11.1%in a dermatologic clinic and increased with time as previous studies show during the period from 1995 to 2005. These studies show an incidence rate of ≤3.8% [1,3,4,5,8] [13], and 4.48 in Erbil for the year 2012 [9].…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…This rate was higher than the previously reported studies for different geographical areas in Iraq, as show incidence rate with a range of 1.2% to 6.86% [3,4,5,8,9,11,12]. However, one study [10] reported incidence rate of 11.1%in a dermatologic clinic and increased with time as previous studies show during the period from 1995 to 2005. These studies show an incidence rate of ≤3.8% [1,3,4,5,8] [13], and 4.48 in Erbil for the year 2012 [9].…”
Section: Discussioncontrasting
confidence: 51%
“…A total of 1639 subjects were included in the study, of them 860 (52.5%) were male and 779 (47.5%) were female, with age range from 1 month to 90 years for male, and 25 days to 80 years for female. Cases of scabies were diagnosed according to conventional criteria [10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Чесотка актуальна и для стран Ближнего Востока. При массовом обследо-вании населения одного из городов Ирака (2007)(2008)) этот паразитоз выявлен в 11,1% случаев [14,15].…”
unclassified